Đề xuất khung năng lực số trong dạy học cho sinh viên sư phạm ở trường đại học - Châu, Thị Hồng Nhự (Tạp chí Giáo dục, 2024)
Digital competence is considered a vital factor to achieve success in study, research and future career development. Digital industries have become a key factor in the economy; for educational institutions to become digital business models, lecturers and students must be the ones to take advantage of the benefits of technology, while supporting the community and promoting innovation and creativity in the next generations. This article proposes a digital competence framework in teaching for pedagogical students at Vietnamese universities to meet the requirements of digital transformation in education and training and the strong impact of the 4.0 Industrial Revolution. The research results aim to effectively exploit the digital environment in teaching, bringing motivation and excitement to learners; contributing to improving teaching quality, forming and developing qualities and competence for students.